Gender diversity in top management team and firm financial performance: empirical evidence from China - Liu, Yixiao (2020)
In the context of the rapid development of the global economy, a diversified top management team helps companies gain competitive advantage. Gender equality is also receiving increasing attention. In recent years, there is an increasing number of researches about gender diversity in top management team and firm financial performance. The findings of the relationship between the gender diversity of firm financial performance is mixed. Most of these studies have been conducted in Europe and America. There are few empirical studies in China on this topic. This dissertation examined the impact of female executives on firm financial performance. The fixed effects model was adopted in this dissertation to perform regression analysis on the three-year panel data of Chinese listed companies. There is a positive relationship in the result of this paper. The findings of this dissertation make contributions to the methods of the company to optimize the structure of top management team.